Extremism and Non-Development: Utilizing Sustainable Development as an Approach to Combat Extremism - Roya Jafari; Mehdi Zakerian Amiri (پژوهشهای حقوقی)
Today extremism and any type of violent activities based on extremist idea have been become to one of the most controversial Threats to international peace and security. Combating this phenomenon is not properly successful by responsive measure, so its recommended by International intuitions that anti-extremist measures need to utilize a comprehensive policy that encompass all dimension and related matters in addition to suppressive measures, the policy has to consider preventive one. One of the most important function relied on preventive measures is recognition extremism causes and roots and its tendency expansion. Researches show non-development and deprivation of soci-economic rights is one of extremism expansion reasons. Focus on sustainable development may employ as a complementary solution in anti-extremist policies. The article concluded that in order to utilize sustainable development for combat extremism, new approach for prioritizing of its Goals is needed and any sustainable development program have to reorganize under the flag of anti-extremism policies.